PENGARUH ROBOT GEOMETRI UNTUK PENGEMBANGAN PEMAHAMAN MATEMATIKA PERMULAAN ANAK USIA 3 – 4 TAHUN DI KB ‘AISYIYAH 29 SURABAYA - Nisak, Khoirun; Abidin, Ratno; Sa’ida, Naili; Gusmaniarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early mathematics is an important foundation in shaping the logical thinking skills of young children. This study examines the effect of the APE Geometry Robot media on the understanding of basic mathematical concepts such as shapes, sizes, and patterns in children aged 3–4 years at KB 'Aisyiyah 29 Surabaya. Through a fun play approach, activities such as matching and grouping help children understand mathematics naturally. This study examines the effect of using the Educational Teaching Aids (APE) Geometry Robot media on the development of early mathematics understanding in 3-4 year old children at KB 'Aisyiyah 29 Surabaya. This study used a quantitative method with a one-group pre-test and post-test pre-experimental design. Data collection techniques included observation and documentation, with assessment indicators covering five aspects of early mathematical ability. The research sample consisted of 31 children. The Wilcoxon statistical test was used to test the effectiveness of the treatment. The results showed a significant increase in children's mathematical abilities after the implementation of the Geometry Robot media, as indicated by the rejection of the null hypothesis (T count = 0 < T table = 8). Interactive and concrete learning media such as the Geometry Robot have been proven to increase children's cognitive engagement, help them understand basic mathematical concepts, and foster logical, critical, and creative thinking patterns from an early age.